Development of Inquiry Students Worksheet to Train High Order Thinking Skills on Chemical Equilibrium Material - Ayu Rosita Eka; Ismono Ismono (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
The purpose of this study is to describe the feasibility of inquiry students worksheet to practice high order thinking skills on chemical equilibrium material. The research method used is the 4-D model including Define, Design, Develop and Dissiminate. This research was limited to the develop stage and then a limited trial was carried out to 12 students of class XI Senor High School 1 Krian. The research instrument used was a review sheet, a validation sheet, a student response questionnaire, a test sheet for learning outcomes in the domain of knowledge and a prestest-posttest question sheet for high order thinking skills. The results obtained showed that the feasibility of students worksheet in terms of content, language, presentation, and graphic criteria got percentage of 85%, 89%, 91% and 91% with very valid categories. Based on this percentage, the developed students worksheet is suitable for use in the learning process. The feasibility of the students worksheet was also supported by a very positive response from students with a percentage of 88.5%. There was an increase in the high order thinking skills test of students with an n-gain score of 0.707 which is in the high category. The percentage of results of each component of high order thinking skills includes analyzing (C4) of 84.3%, evaluating (C5) of 83% and creating (C6) of 87.5% in the high category and declared effective.